2008
DOI: 10.1007/s00108-008-2072-5
|View full text |Cite
|
Sign up to set email alerts
|

Herzrhythmusstörungen bei der Schwangeren und beim Fetus

Abstract: For the acute treatment of supraventricular (SVT) and ventricular tachycardias (VT) in pregnant women, electrical cardioversion with 50-100 J is indicated in all unstable patients. In stable SVT the initial therapy includes vagal maneuvers or intravenous adenosine. For long-term therapy, beta-blocking agents with beta(1)-selectivity are first-line drugs or specific anti-arrhythmic drugs. An implantable cardioverter-defibrillator is another approach. In patients with symptomatic bradycardia, a pacemaker can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Currently, fetal echocardiography is the best method and remains the cornerstone for in utero diagnosis of arrhythmias. [31] It has been shown that the electrophysiologic mechanisms of fetal supraventricular tachyarrhythmias can be clarified with superior vena cava/aorta Doppler flow recordings. [32] For differentiation of supraventricular from ventricular arrhythmia cross-sectional echocardiography, M-mode and echo-Doppler have been used.…”
Section: Fetal Arrhythmias During Pregnancymentioning
confidence: 99%
“…Currently, fetal echocardiography is the best method and remains the cornerstone for in utero diagnosis of arrhythmias. [31] It has been shown that the electrophysiologic mechanisms of fetal supraventricular tachyarrhythmias can be clarified with superior vena cava/aorta Doppler flow recordings. [32] For differentiation of supraventricular from ventricular arrhythmia cross-sectional echocardiography, M-mode and echo-Doppler have been used.…”
Section: Fetal Arrhythmias During Pregnancymentioning
confidence: 99%